Enhanced chlorine dioxide decay in the presence of metal oxides: Relevance to drinking water distribution systems - Liu, C.; Von Gunten, U.; Croué, Jean-Philippe (American Chemical Society, 2013)
Chlorine dioxide (ClO2) decay in the presence of typical metal oxides occurring in distribution systems was investigated. Metal oxides generally enhanced ClO2 decay in a second-order process via three pathways: (1) catalytic disproportionation with equimolar formation of chlorite and chlorate, (2) reaction to chlorite and oxygen, and (3) oxidation of a metal in a reduced form (e.g., cuprous oxide) to a higher oxidation state. Cupric oxide (CuO) and nickel oxide (NiO) showed significantly stronger abilities than goethite (a-FeOOH) to catalyze the ClO2 disproportionation (pathway 1), which predominated at higher initial ClO2 concentrations (56-81 µM). At lower initial ClO2 concentrations (13-31 µM), pathway 2 also contributed. The CuO-enhanced ClO2 decay is a base-assisted reaction with a third-order rate constant of 1.5 × 10 6 M-2 s-1 in the presence of 0.1 g L -1 CuO at 21 ± 1 C, which is 4-5 orders of magnitude higher than in the absence of CuO. The presence of natural organic matter (NOM) significantly enhanced the formation of chlorite and decreased the ClO 2 disproportionation in the CuO-ClO2 system, probably because of a higher reactivity of CuO-activated ClO2 with NOM. Furthermore, a kinetic model was developed to simulate CuO-enhanced ClO 2 decay at various pH values. Model simulations that agree well with the experimental data include a pre-equilibrium step with the rapid formation of a complex, namely, CuO-activated Cl2O4. The reaction of this complex with OH- is the rate-limiting and pH-dependent step for the overall reaction, producing chlorite and an intermediate that further forms chlorate and oxygen in parallel. These novel findings suggest that the possible ClO2 loss and the formation of chlorite/chlorate should be carefully considered in drinking water distribution systems containing copper pipes.